Understanding Internationalization of Higher Education in Indonesia: Prospects and Challenges - Teuku Zulfikar; Emawati Emawati; Amiruddin Amiruddin; Cut Fadhilah Alfa Karim (AT-TA'LIM, 2026)
The internationalization of higher education plays a crucial role in expanding the reach of higher education institutions to a global audience. In order to facilitate the internationalization of the institutions, the university's top management must actively engage in strategic management planning to ensure a smooth and effective internationalization process. This qualitative research examines the efforts made by three state universities in three different contexts to internationalize themselves. The data was gathered through three Focus Group Discussions (FGD), one in each university. The participants of the FGDs were the top management of the postgraduate schools. The data was also gathered through in-depth interviews with some lecturers and the director of international offices. Our research reveals significant findings that universities being researched, use common techniques, yet contextually distinctive, to achieve internationalization goals. These strategies include collaborating on research and publications, hosting visiting lecturers, offering double degrees, appointing adjunct professors, organizing international conferences, and providing research fellowships.